Alcohol Use Disorder Following Bariatric Surgery Leading to Cirrhosis and Hepatorenal Syndrome - Jenna M. Davison; James F. Howick V; Neel Shah (Annals of Internal Medicine: Clinical Cases)
The rise in metabolic surgeries for obesity has increased concerns regarding post-surgical alcohol use disorder (AUD). We present a case of a 51-year-old woman who developed AUD and subsequent alcohol-related cirrhosis after Roux-en-Y gastric bypass surgery. Her sensitivity to alcohol heightened after surgery, leading to addiction. Despite treatment attempts, she developed complications, including hepatic encephalopathy and hepatorenal syndrome, ultimately necessitating hemodialysis. The case underscores the complex interplay between bariatric surgery, AUD, and cirrhosis, exacerbated during the COVID-19 pandemic. Heightened awareness of AUD after bariatric surgery and its complications, including hepatorenal syndrome, is crucial for comprehensive patient care amidst rising rates of obesity and alcohol misuse.